2020
DOI: 10.1051/parasite/2020009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Enterocytozoon bieneusi in farm-raised pigs in Hainan Province, China: infection rates, genotype distributions, and zoonotic potential

Abstract: Enterocytozoon bieneusi is a zoonotic fungal pathogen with a high degree of host diversity that can parasitize many animals, including humans. Pigs may play an important role in the epidemiology of E. bieneusi as reservoir hosts. Nevertheless, the genotypes of E. bieneusi in pigs in China remain poorly understood. The aim of this study was to determine the prevalence of E. bieneusi infection amongst pigs raised on farms from four cities of Hainan Province, using nested polymerase chain reaction (PCR) of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 62 publications
2
24
2
Order By: Relevance
“…bieneusi in wildlife has previously been documented in wild carnivores including European badgers (Meles meles, 23%), beech martens (Martes foina, 11%) and red foxes (Vulpes vulpes, 9-14%) (Galván-Díaz et al, 2014;Santín et al, 2018). EbpA, the most prevalent genotype in this study in Iberian pigs and wild boars, is commonly reported in pig worldwide (Zhou et al, 2020). It was also the most abundant genotype in a survey in wild boar in Central Europe (Němejc et al, 2014) and…”
Section: Discussionsupporting
confidence: 62%
“…bieneusi in wildlife has previously been documented in wild carnivores including European badgers (Meles meles, 23%), beech martens (Martes foina, 11%) and red foxes (Vulpes vulpes, 9-14%) (Galván-Díaz et al, 2014;Santín et al, 2018). EbpA, the most prevalent genotype in this study in Iberian pigs and wild boars, is commonly reported in pig worldwide (Zhou et al, 2020). It was also the most abundant genotype in a survey in wild boar in Central Europe (Němejc et al, 2014) and…”
Section: Discussionsupporting
confidence: 62%
“…Sequence analysis of the internal transcribed spacer (ITS) region of the ribosomal RNA (rRNA) gene has revealed more than 500 genotypes (142 in humans, of which 49 were also identified in animals) [ 11 , 20 , 54 ]. Phylogenetic comparative analyses clustered all genotypes into eleven major genetic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Group 1 or 2 are frequently reported in pets, non-human primates, wildlife, and livestock (pigs, cattle, sheep, etc.) [5,8]. However, the mechanism of transmission of infection from a specific animal to humans is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These studies involved five provinces with infection rates ranging from 3.6% to 35.1% [12][13][14][15][16][17][18][19][20]. In Hainan Province in China there is a high number of rodents that are in close contact with humans and other animals and there is a high prevalence of E. bieneusi in farmed, household, and wild animals [8,9,26,27]. Thus, it is necessary to understand E. bieneusi epidemiology in rodents to prevent pathogen infection in humans as well as in other animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation